New Normal Acceleration Strategy for Bali Tourism Destination Recovery with E-Tourism and Special Health Protocol for the Tourism Sector - Utama, I Gusti Bagus Rai; Junaedi, I Wayan Ruspendi; Krismawintari, Ni Putu Dyah; Pramono, Jaya; Laba, I Nengah (Technium Social Sciences Journal, 2020)
Virtual tourism is accepted make an advantage for bosses small scale of travel industry through the offer of access administrations, however, all in large scale virtual tourism will affect essentially on the travel industry goals in the truth of the experience since they can’t be provided by the supplier. Virtual tourism just give looks and impressions, yet unfit to give a taste, smell, feeling, fulfillment, dedication, and dependability. Arranging a traveler visit may utilize different proposals offered by different suppliers. For booking travel tickets inside the nation, traveloka will be their decision with different advantageous installment choices gave. For booking global travel tickets they may pick TripAdvisor. For the choice of goals to be visited, potential sightseers will no doubt utilize the suggestions offered by Indonesia Virtual Tour, and Tripadvisor may be for determination of facilities, imminent travelers get more suggestions, however, who can show evaluations that are probably going to be trailed by expected voyagers. Regardless of how straight forward virtual tourism is, they have a significant job as an extension between the travel industry makers and likely voyagers. E-tourism created in Indonesia right now has not addressed the most significant part of giving data and assurance to sightseers when they decide to visit vacationer goals. The vast majority of the suppliers that fabricate virtually the travel industry frameworks have the point of building up a business association or business affiliations with entrepreneurs, for example, convenience administrations, tagging administrations, eatery administrations, and different administrations focused on business. Another technique arranged to quicken the recuperation of Bali’s travel industry is to make and set explicit wellbeing gauges. Explicit Health Standards arranged for the travel industry as expressed in Circular Letter Number 3355 of 2020 concerning the new ordinary Protocol for the Bali Tourism Sector.